적립비율 위험(Funding Ratio at Risk) 제약 기반 자산배분 모형 - 김용기(Yong Gi Kim); 김대식(Dae Sik Kim); 이재현(Jaehyun Lee) (한국증권학회지, 2016)
자산중심 접근법에 따른 자산배분의 해는 제도의 특징을 포착하지 못하는 단점이 있다. 잉여수익 접근법(SaR)은 완전적립방식에서의 부채 관점의 자산배분 모형으로 자산중심접근법 모형을개선하고 있다. 그러나 잉여수익 접근법은 부채의 규모가 변동하는 기관에 적용할 경우 신규 차입이나 상환에 따른 부채 규모 변동위험을 적절히 대처하지 못하는 단점이 있다. 이에 본 연구는이러한 부채 규모 변동위험을 포함한 부채의 특징을 헤징하는 방법론인 적립비율 위험제약(FRaR) 기반의 자산배분 모형을 제시하였다. 이 연구에는 frar 모형으로 적립비율 변동성을 최소화하는채권 듀레이션 방안을 제시하여 SaR 모형에서 도출되는 최적 자산 비중과 채권듀레이션을 비교하였다. 그 결과 SaR와 FRaR 모형에서는 공통적으로 적립상태가 개선될수록 위험자산 비중은낮아진다. 또한, 과대(과소) 적립상태에서는 FRaR 모형의 채권 듀레이션이 높다(낮다). 둘째, 두모형 모두에서 부채 듀레이션이 증가할수록 위험자산 비중에는 변화가 없으나 채권듀레이션은증가한다. 셋째, 부채 기대 증가율이 높을수록 SaR 모형과 FRaR 모형에서 과소적립상태에서는위험자산과 채권 듀레이션이 증가하지만 과대적립상태에서는 감소한다. 또한, SaR 모형에서 다룰수 없는 문제들에 대한 분석도 가능한 바 이에 대한 주요 결과는 다음과 같다. 첫째, 부채 증가율의이자율 민감도가 클수록, 위험자산 비중에는 변화가 없으나, 과소 적립상태에서는 채권 듀레이션이감소하고 과대적립상태에서는 증가한다. 둘째, 부채 증가율의 고유 충격 변동성이 클수록, FRaR 모형에서는 위험자산비중과 채권 듀레이션은 감소하지만 SaR 모형은 이러한 특징을 포착하지 못한다. Asset only approach of asset allocation models does not take the characteristics of funding and investment policies into account. Surplus at risk (SaR) approach tries to incorporate the policy aspects into asset allocation decisions, but cannot cope adequately with the situation in which liability changes due to new borrowings or redemptions. This study attempts to overcome these limitations by suggesting a new approach in which funding ratio at risk (FRaR) is used to hedge the liability risks arising from the changes in liability. In particular, we compares the asset allocation decisions and resulting optimal bond duration from this new approach to those from the SaR models. The main findings of this study are as follows. First, as in SaR models, the FRaR approach assigns lower weight in the risky assets as the funding status improves. Second, in an over-funded state, the optimal bond duration under FRaR becomes longer than that uder SaR, and vice versa. Third, as duration of liability increases, without changing the weight of the risky assets, the duration of bonds tends to increase in both models. Fourth, as the expected growth rate of liability increases, both SaR and FRaR models assign a higher weight of the risky assets and longer duration for bonds in under-funded state, while a lower weight and shorter duration in over-funded state. The FRaR approach can also analyze the situations for which the SaR approach is silent about. For example, the SaR approach is silent about the effects of the interest rate sensitivity of liability growth rate. FRaR approach, however, suggests that with a higher interest sensitivity, in an under-funded state, bond duration should be lower without changing the weight of risky assets, while in a over-funded state, higher. Another example has to do with the idiosyncratic risks of liability. The FRaR approach implies that as the idiosyncratic risks becomes higher, the weight of risky assets and bond duration should decrease. The effects of idiosyncratic risks of liability cannot be investigated within the SaR approach. KCI Citation Count: 1